2021
DOI: 10.3390/molecules26175156
|View full text |Cite
|
Sign up to set email alerts
|

Mexican Oregano (Lippia graveolens Kunth) as Source of Bioactive Compounds: A Review

Abstract: Lippia graveolens is a traditional crop and a rich source of bioactive compounds with various properties (e.g., antioxidant, anti-inflammatory, antifungal, UV defense, anti-glycemic, and cytotoxicity) that is primarily cultivated for essential oil recovery. The isolated bioactive compounds could be useful as additives in the functional food, nutraceuticals, cosmetics, and pharmaceutical industries. Carvacrol, thymol, β-caryophyllene, and p-cymene are terpene compounds contained in oregano essential oil (OEO); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 109 publications
0
24
0
1
Order By: Relevance
“…and between 24.82 and 24.95 mm in Pseudomonas fragi . On the other hand, Bautista-Hernández et al [ 67 ] reviewed the antibacterial action of L. berlandieri applied as vapor against E. coli , finding an MIC of 4 μg/mL. All the revised studies showed the antibacterial activity of plant compounds expressing MIC, MBC, or agar diffusion.…”
Section: Efficacy Loss Of Conventional Antibiotics and Proposed Solut...mentioning
confidence: 99%
“…and between 24.82 and 24.95 mm in Pseudomonas fragi . On the other hand, Bautista-Hernández et al [ 67 ] reviewed the antibacterial action of L. berlandieri applied as vapor against E. coli , finding an MIC of 4 μg/mL. All the revised studies showed the antibacterial activity of plant compounds expressing MIC, MBC, or agar diffusion.…”
Section: Efficacy Loss Of Conventional Antibiotics and Proposed Solut...mentioning
confidence: 99%
“…The potential utility of the bioactive compounds present in oregano essential oil extends to the food industry, i.e., as an additive in functional foods, flavoring or nutraceuticals, as well as the agronomic industry, in perfumery and in pharmaceuticals. Recently, it has been studied as a potential inhibitor of COVID-19 [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, Mexico is the second largest producer of oregano, mainly with the species L. graveolens Kunth, L. berlandieri Schauer, and recently, P. longiflora Gray [ 8 , 10 , 23 ], but due to the fact that most of the commercially exploited species are of wild origin and depend on the rainy season for their harvest, as well as being also affected by increasing climatic changes such as long dry seasons [ 5 , 23 ], neither the supply of oregano nor the quality of its essential oil is ensured. Moreover, the natural recovery of this resource is not guaranteed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lippia origanoides se ha utilizado para distintos propósitos, principalmente como saborizante (Salazar et al , 2016 y como planta medicinal (Roys 1931, Linares & Bye 1989, Lewis 1990, Hopkings 2011. La especie es considerada como una fuente importante de compuestos bioactivos (Bautista-Hernández et al 2021). Debido a estas propiedades, la cosecha y comercialización del orégano se ha desarrollado a lo largo de su área de distribución (Soto et al 2007).…”
unclassified